Preliminary study on the adoption of dark fermentation as pretreatment for a sustainable hydrothermal denaturation of cement-asbestos composites. (10th November 2017) - Spasiano, Danilo; Luongo, Vincenzo; Petrella, Andrea; Alfè, Michela; Pirozzi, Francesco; Fratino, Umberto; Piccinni, Alberto F.
Abstract: A harmless cement conglomerate reinforced with glass fibers (GFC), simulating a cement-asbestos composite (CAC), was dissolved into dark fermentation (DF) synthetic and real effluents. The experimental campaign carried out with synthetic DF effluents showed a strong diffusional resistance to volatile fatty acids (VFAs) migration through GFC. However, at the end of the dissolution phase in real DF effluents, a complete dissolution of the GFC cement phase and a final pH equal to 4.71 were achieved by the use of GFC grain size lower than 1.0 mm, GFC load equal to 5.0·10 3  ppm, and glucose as biodegradable substrate. Moreover, during the DF process a whole production of 284 mmolH2 /Lsol was obtained. This investigation represents a preliminary study on the denaturation of CAC, by a DF and hydrothermal treatment train, as promising alternative to the landfilling. Indeed, hydrothermal denaturation of CAC requires, as reported in previous studies, severe and expensive operational conditions and remarkable acid consumption to dissolve the cement matrix. On the other hand, the DF of bio-degradable compounds results in the production of rich in VFAs solutions, which could be used for CAC pretreatment leading to the cement matrix dissolution, and generates bio-hydrogen as a renewable energy source for the hydrothermal phase. Graphical abstract: Image 1 Highlights: A dark fermentation step was proposed before cement-asbestos hydrothermal treatment. Glass fiber cement conglomerate was used to simulate real cement-asbestos samples. Optimal dissolution conditions were obtained using synthetic fermentation effluents. Glass fiber cement mortar (5 g/L) was dissolved in real dark fermentation effluents. Hydrogen from dark fermentation can be used as energy source for hydrothermal phase.